An efficient technique for out-of-band power reduction for the eliminated CP-STC-shaped system for 5G requirements - Mohamed Yasin I. Afifi; Mohamed S. Elbakry; El-Sayed S. A. Soliman; A. A. Ammar (Institute of Advanced Engineering and Science, 2020)
The most dominant needs for the recent wireless mobile applications are higher bandwidth (BW) efficiency, higher energy efficiency higher quality of services (QOS). The main technique in 4G systems is OFDM but it suffers from some limitations such as large peak to average power ratio (PAPR), higher Out-of-Band (OOB) power radiation, and wasting bandwidth efficiency due to cyclic prefix (CP) extension. In his paper, these OFDM limitations will be reduced with low computational complexity compared to filter bank multicarriers (FBMC). The proposed scheme is based on symbol time compression (STC) for OFDM system. The proposed STC-Shaped system is achieved via interleaver-spreader and symbol shaper in the transmitter side in addition to equalization and combining processes in the receiver side. Comparative study between the proposed system and the conventional OFDM in case of additive white Gaussian noise (AWGN) and COST 207 typical multipath fading channel will be presented. The numerical results show that the proposed STC-Shaped scheme reduces OOB significantly. The proposed scheme improves BER in multipath Rayleigh fading although it is without CP. Thus, the proposed system is more robust against inter symbol interference (ISI) compared to conventional OFDM system. Also, the numerical results show that the PAPR of the proposed system is decreased significantly and also, it is derived theoretically. Also, the proposed scheme overcomes CP extension, and hence increases the bandwidth (BW) efficiency. Finally, the computational complexity for the proposed scheme is derived and it has very low complexity compared to FBMC. The system performance measurments has been fulfilled using cumulative distribution function (CDF), power spectral density (PSD) and bit error rate (BER).